O gênero parlenda no 1º ano do ciclo de alfabetização : um olhar sobre a oralidade - Amorim, Crislani Lima de (2024)
Students have contact with oral language long before they reach school age, but it is in the educational process that they will understand the uses of oral language and its relationship with social practice. With the new guidelines and current studies in the area of Linguistics, such as Marcuschi (2008), Schneuwly and Dolz (2004), it is clear that the knowledge acquired at school depends directly on oral, reading and writing skills. In this way, the option for the parlenda genre arose from our studies in the scientific exercise of research and concerns working in the teaching profession, as we found that the characteristics of this genre are coherent with the cultural universe of children, since the parlenda is a short text, contains rhymes, humor, informality, wordplay, verbal/visual language. Based on this, our research has the general objective of understanding the work with orality, from the teacher's perspective, through the observation of practices of the “parlenda” genre, in a 1st year elementary school class. As specific objectives, the research sought to: a) Investigate the teacher's understanding of the role of orality based on practices with the oral genres recommended by BNCC for the literacy cycle. b) Follow classes with the 1st year class of the literacy cycle that focus on the genre of narratives. c) Describe the interaction between teacher-student using the narrative genre in the development of speaking skills in a 1st year class. For theoretical support of the investigation, there was the contribution of scholars such as: Ávila-Nóbrega (2020), when investigating orality in the early years; Carvalho and Ferrarezi (2018), highlighting the teaching of speaking at school; Cavalcante and Marcuschi (2007), when dealing with orality and textual genre; Bakhtin (2016) with language studies; Lima (2008), when addressing the stories; in addition to some official documents that deal with orality, with emphasis on the BNCC (2018), the PNAIC Learning Rights, among others. In the methodology we will have a qualitative and documentary research approach, based on reflections and bibliographical survey, with a descriptive perspective. The method used was field research and data collection took place over the course of a semester in 2023. We also carried out a sociocultural questionnaire, a semi-structured interview and a record of the filming of a week of classes in the 1st grade class. literacy. The analyzes showed that the parlenda genre can be an important resource in the development of oral practices, as this oral genre contributes to the child's phonological construction with the perception of rhythm and rhymes and the recognition of sounds and letters. Thus, it provides the student with the opportunity to acquire oral skills and insertion into the language modalities, through playfulness, play and protagonism with the oral and written forms of the language.